The impact of CD6 targeting in T cell function and immunopathology - Freitas, Raquel Filipa Reis de (2020)
In the last few decades, monoclonal antibodies have become one of the most widely used classes of therapeutic agents, representing a billion-dollar industry with more than 30 monoclonal antibodies approved for human therapeutics and many others under clinical evaluation.1 Their main advantages regarding other therapeutic agents consist of high specificity and high flexibility, which applied against targets involved in immune synapse will enhance its immunomodulatory therapeutic benefits. CD6 an immune synapse transmembrane glycoprotein, important for the stability of antigen presentation, maturation of immunological synapse and optimal T-cell proliferation, has been revived as a therapeutic target since the creation of a nondepleting anti-CD6 mAb in the early '90s. Despite CD6 has been extensively studied, understanding its biology has been difficult due to paradoxical results. Still, one thing is for sure, which is its role in autoimmune pathologies, as it is the case of Multiple Sclerosis, Rheumatoid Arthritis, and Psoriasis. And an example of CD6 paradoxical impact is, while in experimental autoimmune encephalomyelitis (EAE) and imiquimod-induced psoriasis CD6-deficient mice show disease protection or attenuation, in collagen-induced arthritis (CIA) the absence of CD6 made it even worst. So, we have decided to take advantage of this new non-depleting mAb against CD6 d1, developed by our collaborators in Cuba and try to understand how targeting CD6 would impact T cell functional properties and how it would interfere in immune pathologies. Here, I show how both murine and human antibodies targeting CD6 domain 1 influenced exactly that. First, we have investigated how targeting CD6 with our mAb would affect the normal development of a mouse model of MS, to do so we used a well-established EAE model, which had already been used in the lab. Treatment with anti-CD6 was intriguing, since the outcome was heavily related to the dose being used, meaning while a low dose was protective, high doses showed a level of disease severity equivalent or even worse than the control group. However, our mice results do resemble the reports on RA clinical trials, where lower doses were the ones giving longer-term responses. To uncover the mechanisms behind it, we investigated how CD6 targeting was affecting CD4+ T cell functional specialization. And accordingly, to our in-vitro results, we verified that once more, in a dose-dependent manner, while increasing doses were compromising Tregs polarization, in the case of Th1's it was favoring it. To try to exclude a possible steric hindrance effect due to the mAb size, we used a soluble CD166 (CD6 d3 ligand) as a means to disrupt T cell's CD6 interactions with APC's CD166. However, this did not mimic CD6 targeting with our anti-CD6 d1 mAb, suggesting a steric hindrance independent effect. More, targeting CD6 with our mAb suggests a direct effect over signaling itself, since its modulatory properties are only detectable if under activating physiologic conditions. Under supra-physiologic stimulation like with anti-CD3/anti-CD28, the impact over polarization is lost. We expected the impact of anti-CD6 d1 to be a fine-tuned one since no major alterations were seen on either T cell survival or proliferation. Following the rationale of this dose-dependent effect caused by CD6 targeting, we decided to explore its therapeutic potential on other disease models with opposite kinetics to autoimmune diseases. So, we investigated if in a model of breast cancer, high doses of anti-CD6, given under different delivery strategies, would result in total tumor clearance or reduced tumor growth. Our results ended up showing a reduced growth tumor ability if given in in-situ cumulative doses. However, the way CD6 targeting specifically impacted the CD4+ T cell population was not very conclusive due to the lack of statistical significance. But once more the data suggested a negative impact over CD25+Foxp3+ regulatory T cells, specifically tumor-infiltrating ones. Another observation was a potential increase of IL-17 expression by these very same infiltrating Tregs which has been associated with MAPK activation pathways also associated with CD6 activation. Under these same conditions our data also suggests, a negative impact of CD6 targeting over CD4+ T cell activation as measured by CD25 MFI levels, a relation previously reported on human cells by literature. To validate the mice anti-CD6 d1 mab as an adequate proxy of itolizumab, we have also investigated how Itolizumab would impact CD4+ T cell's functional properties in-vitro. And as expected, when treated with anti-CD6 d1, human cells also displayed a dose-dependent negative impact over Treg polarization while on the other side favoring Th1's. But contrary to mice, and despite no impact on survival, targeting CD6 did significantly impact. Besides that, human data also suggested a steric hindrance independent effect and dependence on physiological activation conditions so that an impact on T-cell functional properties could be perceived. Activation strategies like anti-CD3/anti-CD28 or SAg mix and APCs, precisely because did not allow an impact of anti-CD6 d1 on CD4+ T cells, shed some light into which signaling pathways anti-CD6 d1 was affecting. Overall our data show a dose-dependent impact of anti-CD6 d1 over T cell functional specialization, meaning while increasingly high doses reduce T cell's polarization ability towards Tregs also favors Th1 induction, something true for both murine and human cells. A potential explanation for such observations is the relation between activation levels and polarization sensitivity, so different activation levels caused by CD6 targeting might favor specific polarization phenotypes. Our data highlights the importance of dosage and how the same drug might be beneficial for different disease conditions.